Peran Teknologi Pendidikan dalam Pembelajaran - Non Syafriafdi (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2020)
Educational technology is a complex and integrated process that involves people, procedures, ideas, tools and organizations to analyze problems related to all aspects of human learning, and then plan, implement, assess and manage problem-solving efforts. Educational technology is the application of scientific knowledge in learning so that learning objectives can be achieved effectively and efficiently, which are not only limited to tools and goods or hardware but also software, and brainware. The educational technology area includes design, development, utilization, management and assessment. Educational technology plays a role in increasing educational productivity, providing educational possibilities that are more individual in nature, providing a more scientific basis for learning, increasing learning abilities by expanding the range of presentation, enabling more intimate learning, enabling the distribution of quality education.